Accidental Dural Tears in Minimally Invasive Spinal Surgery for Degenerative Lumbar Spine Disease - Aspalter, Stefan; Senker, Wolfgang; Radl, Christian; Aichholzer, Martin; Aufschnaiter-Hießböck, Kathrin; Leitner, Clemens; Stroh, Nico; Trutschnig, Wolfgang; Gruber, Andreas; Stefanits, Harald (Frontiers in Surgery, 2021)
Backgroundː One of the most frequent complications of spinal surgery is accidental dural tears (ADTs). Minimal access surgical techniques (MAST) have been described as a promising approach to minimizing such complications. ADTs have been studied extensively in connection with open spinal surgery, but there is less literature on minimally invasive spinal surgery (MISS). Materials and Methodsː We reviewed 187 patients who had undergone degenerative lumbar spinal surgery using minimally invasive spinal fusions techniques. We analyzed the influence of age, Body Mass Index (BMI), smoking, diabetes, and previous surgery on the rate of ADTs in MISS. Resultsː 22 patients (11.764%) suffered from an ADT. We recommended bed rest for two and a half to five days, depending on the type of repair required and the amount of cerebrospinal fluid (CSF) leakage. We could not find any statistically significant correlation between ADTs and age (p = 0.34,), BMI (p= 0.92), smoking (p = 0.46), and diabetes (p = 0.71). ADTs were significantly more frequent in cases of previous surgery (p < 0.001). None of the patients developed a transcutaneous CSF leak or postoperative infection. Conclusionsː The frequency of ADTs in MISS appears comparable to that encountered when using open surgical techniques. Additionally, MAST produces less dead space along the corridor to the spine. Such reduced dead space may not be enough for pseudomeningocele to occur, cerebrospinal fluid to accumulate, and fistula to form. MAST, therefore, provides a certain amount of protection.